2022
DOI: 10.3233/nre-220007
|View full text |Cite
|
Sign up to set email alerts
|

Does acupuncture therapy improve language function of patients with aphasia following ischemic stroke? A systematic review and meta-analysis

Abstract: BACKGROUND: Aphasia is one of the most common complications in patients with ischemic stroke. Studies have shown that acupuncture can improve the symptoms of aphasia patients. However, the effect of acupuncture on language function in patients with ischemic stroke is still controversial. OBJECTIVE: This study aimed to critically assess the efficacy and safety of acupuncture for aphasia following ischemic stroke. METHODS: PubMed, Embase, Cochrane Central Register of Controlled Trials, Web of Science Core Collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…These results suggested that rTMS ameliorated spontaneous language capability in patients in acute and recovery stages. Acupuncture therapy constitutes a significant component of complementary and alternative medicine, which has potential therapeutic effects in the treatment of PSA ( 81 ). The combined therapeutic application of acupuncture and rTMS on NFA has demonstrated a markedly superior efficacy compared to monotherapy.…”
Section: Resultsmentioning
confidence: 99%
“…These results suggested that rTMS ameliorated spontaneous language capability in patients in acute and recovery stages. Acupuncture therapy constitutes a significant component of complementary and alternative medicine, which has potential therapeutic effects in the treatment of PSA ( 81 ). The combined therapeutic application of acupuncture and rTMS on NFA has demonstrated a markedly superior efficacy compared to monotherapy.…”
Section: Resultsmentioning
confidence: 99%
“…However, these three studies did not significantly assess the safety of acupuncture. In the same year, a meta-analysis suggested that acupuncture might have a beneficial effect on aphasia after IS, particularly during the subacute phase [28] . However, the sample sizes of these meta-analyses were insufficient, thereby limiting the results.…”
Section: Evidence From Clinical Studiesmentioning
confidence: 99%
“…Clinical trials and meta-analyses have shown that acupuncture effectively reduces mortality and prevents complications. The meta-analysis results suggest that acupuncture may play an active role in impairment and rehabilitation associated with the onset of IS, including dyskinesia [24] , dysphagia [25] , spasticity [26] , cognitive impairment [27] , aphasia [28] , insomnia [29] , dysarthria [30] , depression [31] , and fatigue [32] . In addition, acupuncture not only intervenes in IS as a therapeutic tool but can also be involved in the induction of ischemic tolerance as a preventive strategy [33] .…”
Section: Introductionmentioning
confidence: 99%
“…This process ultimately leads to the restructuring of neural connections and the restoration of functional abilities. Furthermore, a systematic review ( Sang et al, 2022 ) has indicated that acupuncture therapy administered during the sub-acute phase of ischemic stroke may improve language function in individuals with aphasia. Moreover, another systematic review ( Wang et al, 2012 ) has demonstrated that scalp acupuncture exhibits superior efficacy in terms of improving neurological deficit scores and clinical effectiveness compared with western conventional medicine in patients with ACI.…”
Section: Introductionmentioning
confidence: 99%